THE USE OF MARKETING STRUCTURE IN COMMODITY-INNOVATION POLICY OF ORGANIZATION - Данилюк, Евгения Валентиновна; Рыбак, Анатолий Иванович (Eastern-European Journal of Enterprise Technologies, 2013)
The article reveals the essence of project method at food production enterprise. It presents basic tools for launching new product. The article is based on practical application of these tools at coffee products manufacturing enterprise. Search for effective, cost-effective (temporal and raw materials) resources for market introduction and production of new modified and improved commodities have become one of the major tasks of the commodity and innovation policy, innovation marketing APP (application program package). Introducing the project method of operation to launch new product has become one of the new directions in operating activities of the enterprise. Innovation marketing has two directions – marketing new product and modernization of existing commodity. Innovation marketing includes strategic and operational (tactical) components. Of course there are gaps and risks like negative perception or lack of active perception of new product by the market, there is insufficient amount of all types of resources.